Religious dances and tourism: perceptions of the “tribal” as the repository of the traditional in Goa, India - Pereira, C. (Etnográfica, 2017)
What changes occur in the identity of a group considered tribal in India through the performance of their dances? What is the influence of tourism on their religious cults? How are they perceived by other Indians? To answer these questions, first I analyze how the Goan government sought to institutionalize these tribal dances. Second, I examine the gains in the group’s political, economic and cultural capital through this transition to the tourism industry. The article is based on long ethnographic research in Goa and the topic of folk musical heritage is approached from the perspective of anthropology. Its goal is to shed light on the relatively unknown musical heritage of the Catholic Gawda, also known as Kunnbi. It proposes that through tourism the Gawda, while still tribal, have become appreciated as a repository of traditional Goa, rather than pejoratively considered primitive (associated with backwardness) as they were regarded before, for keeping their village lifestyle. However, once the Catholic Gawda gained visibility vis-a-vis tourists and Goans themselves, thus becoming modern and global, they became paradoxically regarded as the continuers of ancestral practices. There is therefore a process of “invention of tradition,” not so much as in the sense of creating what is revealed to tourists (although there is a standardization for the public), but rather in the interpretation of the Gawda who now represent an authentic Goan identity in their dancing.